India the Future of Fin-tech Boom (A Research on Future Perspective): The Growing Influence and Future Prospects of FinTech in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The concept of fin tech is gaining momentum in India. Things like UPI (Unified Payments Interface) based payments have been developed. The popularity of the technology used for making payments and transfer of funds and transactions are advancing to meet the needs of the modern business and commerce and industry. Global giants like Google, Samsung, Amazon have introduced (UPI) system in to their businesses. Even digital payment firms like Paytm, PhonePe, Mobwik and Free charge are strengthening themselves. India is largest online payments and mobile wallet company. Even company like Flip kart is planning to invest 500 million dollars to scale up its technology. Even the research companies expect that in India digital platform will be best used by 2023. All these things could be possible because of fin tech technology use. The current research paper focuses on the pros and corns and the future perspectives in India in the field of use of fintech technology.